2001
DOI: 10.1002/ijc.1017
|View full text |Cite
|
Sign up to set email alerts
|

Clinical staging of prostate cancer: Reproducibility and clarification of issues

Abstract: SUMMARY The American Joint Committee on Cancer (AJCC) staging system for prostate cancer adopted in 1992 is based on tumor-node-metastasis (TNM) designations. It has been widely accepted for use in local and advanced disease. The purpose of this study was to assess reproducibility of staging among observers and to help clarify staging issues. Twelve prostate cancer cases were sent to 20 physicians with special expertise in prostate cancer including eight urologists, eight radiation oncologists, and four medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 39 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…The mean age of all participants was 63.2 years (± 8.5), which is within ± 5 years from the matched controls (58.5 ± 10.8). Five of the 16 participants had T2a clinical T-stage of their prostate cancer, two had a T1c stage, and the rest had a T2b to T3c stage (N = 9/16) (Campbell et al, 2001). Six patients (38%) had a Gleason score of 9 and 10 patients had Gleason scores between 6 and 8.…”
Section: Resultsmentioning
confidence: 99%
“…The mean age of all participants was 63.2 years (± 8.5), which is within ± 5 years from the matched controls (58.5 ± 10.8). Five of the 16 participants had T2a clinical T-stage of their prostate cancer, two had a T1c stage, and the rest had a T2b to T3c stage (N = 9/16) (Campbell et al, 2001). Six patients (38%) had a Gleason score of 9 and 10 patients had Gleason scores between 6 and 8.…”
Section: Resultsmentioning
confidence: 99%
“…An important piece of meta-data is the method used to identify the classes of the sample, including the expected accuracy of that method. Many diagnosis methods (e.g., grade of cancer Campbell et al 2001) are far from 100% accurate, and this is obviously going to affect the later data analysis. In addition a particularly important issue that can cause confounding or bias (Broadhurst and Kell 2006;Ioannidis 2005;Ransohoff 2005) is the likelihood that 'cases' will be often be taking considerably more pharmaceutical drugs than are the 'matched' 'controls.'…”
Section: Design Of Experiments (Doe)mentioning
confidence: 99%
“…Furthermore, over 80% of PCas are multifocal, which makes accurate clinical staging even more difficult and unreliable 7 . Clinical tumour understaging has consistently been shown to range from 40% to 60% 8–11 . This is clearly attributable to the multifocal, histologically heterogeneous nature of prostatic carcinoma.…”
Section: Clinical Staging Versus Pathological Stagingmentioning
confidence: 99%
“…7 Clinical tumour understaging has consistently been shown to range from 40% to 60%. [8][9][10][11] This is clearly attributable to the multifocal, histologically heterogeneous nature of prostatic carcinoma. Bostwick et al found that 59% of clinical stage T2, T3 and T4 PCas in men undergoing radical prostatectomy were understaged when compared with final pathological stage.…”
Section: Clinical Staging Versus Pathological Stagingmentioning
confidence: 99%